SITI'S PERSONALITY IN THE NOVEL TERUSLAH BODOH JANGAN PINTAR BY TERE LIYE - Tarina Roliani; Rheisa Nurfariza Zachra (Fakultas Ilmu Budaya and LPPM Universitas Sebelas April, 2025)
This study analyzes the character Siti in Tere Liye’s novel Teruslah Bodoh Jangan Pintar against the backdrop of corruption among educated individuals, highlighting the societal shift that prioritizes academic intelligence over ethical values. Employing a descriptive qualitative approach, this research examines Siti’s personality through the lens of Freud’s psychoanalytic theory, focusing on the dynamics of the id, ego, and superego. The findings reveal that Siti’s character is influenced by impulsive emotional responses (id), rational considerations (ego), and moral values (superego), illustrating her internal conflict between personal ambition and ethical demands. Additionally, the analysis uncovers how Siti’s experiences reflect broader themes of social pressure, the glorification of intelligence, and the importance of integrity in character formation. Data is collected through a close reading of the novel, identifying and classifying instances that exemplify the id, ego, and superego, as well as the moral crisis faced by the character. The research concludes that Siti embodies a complex interplay of emotional drives, rational thought, and ethical considerations, ultimately contributing to a deeper understanding of the moral implications presented in Tere Liye’s work.